2017
DOI: 10.1037/apl0000195
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic and Asian performance on selection procedures: A narrative and meta-analytic review of 12 common predictors.

Abstract: Hispanics are both the largest and fastest growing minority group in the U.S. workforce. Asians also make up a substantial and increasing portion of the workforce. Unfortunately, empirical research on how these groups perform selection procedures appears to be lacking. To address this critical gap, we identified and reviewed research from a variety of literatures relevant to Hispanic and/or Asian performance on 12 commonly used staffing procedures. We also contacted authors of studies that included members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 128 publications
2
37
0
Order By: Relevance
“…Thus, gender was negatively related to task performance and OCB; in other words, females obtained slightly higher scores than males on task performance and OCB and effect size reached the minimum on task performance, but not on OCB. This is somehow consonant with some of the literature (e.g., Ali & Davies, 2003;Kidder & McLean, 2001;Lovell et al, 1999;Roth et al, 2017), which also found that females tend to obtain higher scores on task performance and OCB. It can be argued that this results may be explained because women are stereotyped as compassionate, kind, and helpful (e.g., Eagly, 1987;Heilman, 1983), researchers have predicted that women, more frequently than men, will engage in OCB related to helping others.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, gender was negatively related to task performance and OCB; in other words, females obtained slightly higher scores than males on task performance and OCB and effect size reached the minimum on task performance, but not on OCB. This is somehow consonant with some of the literature (e.g., Ali & Davies, 2003;Kidder & McLean, 2001;Lovell et al, 1999;Roth et al, 2017), which also found that females tend to obtain higher scores on task performance and OCB. It can be argued that this results may be explained because women are stereotyped as compassionate, kind, and helpful (e.g., Eagly, 1987;Heilman, 1983), researchers have predicted that women, more frequently than men, will engage in OCB related to helping others.…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, those studies should also further analyze the nature of subgroup differences in applicant scores in different job domains. Finally, past applicant samples mainly incorporated Whites and Blacks and, hence, they did not contribute to our knowledge related to other ethnic subgroups such as Asians, a group that has received notably less attention than other minority groups (see Bobko & Roth, ; Lievens & De Soete, ; Roth, Van Iddekinge, et al, ). Similarly, we could find no applicant studies of sex differences on SJT scores in the applied psychology literature.…”
Section: Study Backgroundmentioning
confidence: 96%
“…Over the past years, this need for accurate information about subgroup differences in personnel selection procedures has generated a substantial amount of research, resulting in several narrative summaries and meta‐analyses with special attention given to subgroup differences across ethnicities (Bobko & Roth, ; Dean, Roth, & Bobko, ; Hough, Oswald, & Ployhart, ; Huffcutt & Roth, ; Lynn & Irwing, ; Ployhart & Holtz, ; Roth, Bevier, Bobko, Switzer, & Tyler, ; Roth, Bobko, McFarland, & Buster, ; Roth, Van Iddekinge, et al, ; Whetzel, McDaniel, & Nguyen, ).…”
Section: Study Backgroundmentioning
confidence: 99%
“…a Based on our first-order meta-analysis only. b Based on a second-order meta-analysis which is an aggregate of our first-order meta-analysis and a published meta-analysis, specificallyRoth et alc Based on a second-order meta-analysis which is an aggregate of our first-order meta-analysis and a published meta-analysis, specificallyRoth et al's (2017) SAT (g) results. d Based on previously published meta-analysis only, specificallyHuffcutt et al (2001).…”
mentioning
confidence: 99%
“…As indicated in the Uniform Guidelines, the alternative must also be equally valid(EEOC, 1978). However, the focus of this study is on using different methods to measure the same or similar constructs and producing smaller subgroup differences, and not the validity evidence for the different methods.3 We coded for White-Asian American differences but there was an insufficient number of data points to permit their inclusion in the study (i.e., all but 2 of the 44 alternative method cells in Tables 1-3 were empty).4 We were unable to includeRoth et al's (2017) meta-analysis because their results were not presented at the level that permitted a construct × method level of analysis.…”
mentioning
confidence: 99%